2019
DOI: 10.1016/j.ijid.2019.02.044
|View full text |Cite
|
Sign up to set email alerts
|

The need for an antibiotic stewardship program in a hospital using a computerized pre-authorization system

Abstract: Objectives: Antimicrobial stewardship programs (ASPs) have an important role in the appropriate utilization of antibiotics. Some of the core strategies recommended for ASPs are pre-authorization and prospective audit and feedback. In Turkey, a unique nationwide antibiotic restriction program (NARP) has been in place since 2003. The aim of this study was to measure the effect of a prospective audit and feedback strategy system along with the NARP. Methods: A prospective quasi-experimental study was designed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another disadvantage of pre-authorization is the need for a full-time ID physician consultation. However, it usually provides stricter control of antimicrobial usage (7). We observed that physicians consider the decrease in antimicrobial resistance as the most relevant impact of implementing ASPs.…”
Section: ' Discussionmentioning
confidence: 87%
“…Another disadvantage of pre-authorization is the need for a full-time ID physician consultation. However, it usually provides stricter control of antimicrobial usage (7). We observed that physicians consider the decrease in antimicrobial resistance as the most relevant impact of implementing ASPs.…”
Section: ' Discussionmentioning
confidence: 87%
“…To assess the impact of ASP interventions, 24 studies (45%, 24/53) assessed clinical or patient-centered outcomes [ 62 64 , 66 , 67 , 69 , 73 75 , 77 , 79 81 , 86 88 , 97 , 100 104 , 106 108 ]. Metrics used to evaluate the intervention included length of stay in hospital (LOS) in specific units (e.g., ICU) [ 46 , 62 , 68 , 69 , 73 , 74 , 76 , 77 , 81 , 86 , 88 , 96 , 101 103 ], hospital mortality [ 62 , 76 , 77 , 80 , 86 , 100 102 , 106 ], rehospitalization [ 77 , 81 , 83 , 86 , 104 ], hospital-acquired infections [ 63 , 64 , 67 , 81 , 97 , 107 , 109 ], and device-associated infections [ 64 ]. ASPs brought about positive clinical outcomes in hospital inpatients in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…Studies also documented a reduction in the incidence of bacterial infections such as Clostridioides difficile infections and Candidemia [ 75 , 77 ], and a decrease in pan-drug resistant isolates [ 65 , 71 , 77 , 85 ]. Economic outcomes were assessed in 17 studies [ 39 , 65 , 69 , 71 , 81 , 86 , 88 90 , 93 , 94 , 96 , 100 , 103 , 104 , 107 , 110 ], and reported a decrease in hospital antibiotic procurement cost [ 65 , 71 , 81 , 90 , 93 , 94 ], savings in antibiotic costs [ 39 , 69 , 86 , 88 , 104 , 110 ], decrease in antibiotic therapy and antibiotic prophylaxis cost [ 67 , 107 ], and hospitalization costs [ 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feedback interventions are the act of providing knowledge of the results of a behavior or performance to an individual [31, 32]. Feedback interventions can change behavior and improve performance and outcomes [16, 33]. Physicians who entered the intervention group received 3 feedback measures, including a real-time warning pop-up message, a 10-day antibiotic prescription feedback, and distribution of educational brochures.…”
Section: Methods Designmentioning
confidence: 99%